Interpreting the API. - Marshall, Ronald M. (The Accounting Review, 1975)
Presents a study which aimed to examine the interpretations of the Abnormal Performance Index (API) in an effort to clarify the extent to which these can be used to justify or rationalize the API as a research technique. Definition of API as applied in studies on the relationship between abnormal security return and earnings under selected accounting alternatives; Expected value of the API; Expected value computations under the association interpretation of API.